Studi Komparasi Hasil Belajar Antara Model Pembelajaran Number Head Together Dan Student Teams Achievement Division (Stad) Mata Pelajaran Matematika Siswa Kelas III SD Unggulan Daar El Dzikir Sukoharjo 2015/2016 - Prasetyaningsih, Wiwik Hari, Drs. Saring Marsudi, SH. M.Pd (2016)
The Background of this problem is the study of mathematics is not using cooperative learning model. Actually, there are many other learning models that can be used to improve learning outcomes of mathematics, such as learning models Number Head Together (NHT) and Student Teams Achievement Division (STAD). This study aims to determine (1) differences in the use of student learning outcomes and learning model NHT learning model STAD in Class III Elementary Scholl Unggulan Daar El Dzikir Sukoharjo 2015/2016. (2) learning outcomes better math between the use NHT learning model and learning model STAD class III Elementary School Unggulan Daar El Dzikir Sukoharjo 2015/2016. This study was an experimental study. The sample in this study were all students of class III A and III B Elementary School Unggulan Daar El Dzikir Sukoharjo 2015/2016. The data collection technique used is the technique of writing tests (matter) and documentation. Techniques of analysis, normality and homogeneity test. Based on the results of data analysis with a significance level of 5% obtained t> t table, ie 4,674 > 2,002 with the average value of learning outcomes math class III B is greater than the class III A, ie 88,333 > 8,.667. The conclusion of this study are as follows: (1) There are differences in the results of students' mathematics learning class III Elementary School Unggulan Daar El Dzikirr Sukoharjo 2015/2016 between using NHT learning model that uses the learning model STAD, (2) Model of STAD is better than NHT learning model to improve mathematics learning outcomes in grade III Elementary School Unggulan Daar El Dzikir Sukoharjo 2015/2016.